2004
DOI: 10.1108/09600030410567478
|View full text |Cite
|
Sign up to set email alerts
|

Securing the upstream supply chain: a risk management approach

Abstract: Supply managers must manage many risks in their increasingly competitive environments. Traditionally this meant buffering against uncertainties, which sub-optimized operational performance. Risk management can be a more effective approach to deal with these uncertainties by identifying potential losses. This conceptual study proposes that situational factors-degree of product technology, security needs, the relative importance of the supplier, and the purchasers' prior experience with the situation should be t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
259
0
7

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 364 publications
(269 citation statements)
references
References 16 publications
3
259
0
7
Order By: Relevance
“…The proposed approach to supply chain risk modelling accentuates the complex nature of risk behavioural interactions. Giunipero and Eltantawy (2004) identified the need for investing in extensive risk management systems for holistic supply chain management. The fundamental objective of the research reported in this paper was to develop a holistic risk management approach to measure overall risk behavioural performance.…”
Section: Resultsmentioning
confidence: 99%
“…The proposed approach to supply chain risk modelling accentuates the complex nature of risk behavioural interactions. Giunipero and Eltantawy (2004) identified the need for investing in extensive risk management systems for holistic supply chain management. The fundamental objective of the research reported in this paper was to develop a holistic risk management approach to measure overall risk behavioural performance.…”
Section: Resultsmentioning
confidence: 99%
“…The only significant exception is reported in [30], who claimed that e-procurement reduced TCs by approximately 99.7%. However, it is likely that such a figure disregards various costs connected to e-procurement.…”
Section: Research Objectivesmentioning
confidence: 98%
“…In order to overcome the limitation of the existing research methods, the research proposed an identification model based on PSO-a population-based random optimization method. Through a comparison of performance with a FCMM, the findings indicated PSO can predict the logistic risk more accurately [4]. From the test results, it is shown that model of risk analysis and identification of logistic risk based on PSO algorithm is superior to FCMM model.…”
Section: Introductionmentioning
confidence: 95%